Phytosociology of the stratum the woody regenerating in Caatinga area, Baixio- CE - Lima, Eliane Gomes de; Barbosa, Veralucia Santos (Revista Ecologia e Nutrição Florestal - ENFLO, 2018)
The Caatinga is one of the most degraded ecosystems from an environmental point of view and the least known with regard to the dynamics of vegetation and ecological processes that occur. With the objective of determining the floristic composition and structure of the plant community in a regenerating Caatinga fragment, this work was developed in backlands depression area, located in the community of Sítio Cigano, Baixio-CE. The data collections were carried out in three distance gradients, starting at the edge and going towards the interior of the fores.They were plotted three fixed plots of 10 m x 10 m for each gradient and included all individuals of shrub-arboreal species with CAP (circumference at breast height) ≥ 10 cm and height ≥ 1,5 m. 64 individuals were sampled distributed in four families, five genera and five species for the I gradient; 77 individuals in four families, eight genera and eight species to the II gradient; and 49 individuals distributed nine families, 13 genera and 13 species for III gradient. Fabaceae was the family with greater wealth and abundance of species in the three gradients. The most abundant species with largest importance value were Croton sp. for the I gradient, Bauhinia cheilantha (Bong.) Steud. for the II gradient and Poincianella pyramidalis (Tul.) L. P for the III gradient. It was registered a greater diversity to the III gradiente. The predominance of initial secondary species in the whole area indicates a slow regeneration.